From vulnerability to growth: strengthening intrapersonal capacity to overcome the quarter life crisis - Deetje Josephine Solang (Jurnal Konseling dan Pendidikan, 2025)
This study examines the Quarter-Life Crisis (QLC) as a psychological phenomenon experienced during the transition to early adulthood, highlighting the significance of intrapersonal capacity as a key factor in transforming vulnerability into growth. Employing a literature review method, the research analyzes recent studies on internal factors such as self-regulation, self-reflection, inner dialogue, and meaningful goal-setting. The findings indicate that intrapersonal capacity functions both as a mediator and a moderator, enabling individuals not only to reduce the negative effects of QLC but also to build psychological resilience and a clearer sense of life direction. This study expands the theoretical perspective of QLC by positioning intrapersonal capacity as a central mechanism, while also offering practical implications for counseling, education, and self-development interventions for young adults.